ANALISIS PEMASARAN KELAPA DALAM (Cocos Nucifera) DI KECAMATAN V KOTO KAMPUNG DALAM KABUPATEN PADANG PARIAMAN - Beben Oktadinanda; Ermi Tety; Eliza Eliza (Indonesian Journal of Agricultural Economics, 2022)
This study aims to determine the form of marketing channels, marketing margins, costs, profits, efficiency and farmer share in each marketing channel. This research was conducted in District V Koto Kampung Dalam, Padang Pariaman Regency. Taking as many as 30 farmer respondents, four regional traders, six inter-regional traders and 11 retailers. The results showed that there are four marketing channels, the largest total marketing margin of all existing marketing channels is in marketing channel II, which is Rp. 4200/grain for grade A coconut and Rp. 2800/grain for grade B coconut. The largest total marketing cost is in marketing channel II, which is Rp. 1183.32/item. The biggest total marketing profit is in marketing channel I, which is Rp. 4923.8/grain for grade A coconut and Rp. 2923.8/grain for Grade B coconut. The most efficient marketing channel is marketing channel III with an efficiency value of 17,9% for grade A coconut and 25.58% for grade B coconut. The highest farmer share value is in Channel III, which is 37.6%/grain for grade A coconut. While the highest farmer share value is for grade B coconut, which is 40%/grain. items contained in the IV marketing channel.